2009
DOI: 10.1590/s0103-90162009000300014
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen supply to corn from sunn hemp and velvet bean green manures

Abstract: Due to their nitrogen fixation potential, legumes represent an alternative for supplying nutrients, substituting or complementing mineral fertilization in cropping systems involving green manuring. The objective of this study was to evaluate the N balance in a soil-plant system involving green manures [sunn hemp (Crotalaria juncea L.) and velvet bean (Mucuna aterrima Piper & Tracy)], both labeled with 15 N. They were incorporated into two soils of contrasting textural classes: a clayey Eutrudox and a sandy-cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 24 publications
0
23
0
2
Order By: Relevance
“…In a pot experiment, Ambrosano et al (2009) observed that maize plants took up more N from sunn hemp incorporated to a sandy soil (Paleudalf) than to a clayey soil (Eutrudox) and that the N derived from the roots was more recalcitrant than that of the shoots. Between 50 and 68% of the 15 N of the sunn hemp shoots remained in the soil whereas the figures for roots varied from 65 to 80%.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…In a pot experiment, Ambrosano et al (2009) observed that maize plants took up more N from sunn hemp incorporated to a sandy soil (Paleudalf) than to a clayey soil (Eutrudox) and that the N derived from the roots was more recalcitrant than that of the shoots. Between 50 and 68% of the 15 N of the sunn hemp shoots remained in the soil whereas the figures for roots varied from 65 to 80%.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…The amounts of N fixed from the atmosphere by diazotrophic bacteria associated with legumes may be substantial and vary from 30 to more than 200 kg ha -1 N (Herridge et al, 2008, Silva et al, 2008. Ambrosano (2009) studied the fate of nitrogen from green manure legumes and found that the efficiency of using this nitrogen source by maize was 30%, for the above-ground part of sunn hemp incorporated to an Ultisol. Trivelin et al (1995; showed that sugarcane recovery values of nitrogen applied in a mineral form ranged from 19 to 40%.…”
Section: Introductionmentioning
confidence: 99%
“…The use of vigorous seeds is essential for ensuring economic viability and sustainability of agro-ecosystems, specially for species such as sunn hemp (Crotalaria juncea L.), which has contributed to performance of various crops: coffee (RICCI et al, 2005), rice (JESUS et al, 2007), sugarcane (DUARTE-JUNIOR & RABBIT, 2008) and maize (AMBROSANO et al, 2009). Sunn hemp also contributes to control weeds and nematodes (COLLINS et al, 2008) in addition to reduction of agricultural inputs used, because it can provide considerable amount of nitrogen for other crops (DINIZ et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, Ambrosano et al (2009) reported values between 40 and 42.4% of N derived from aerial parts of C. juncea and velvet bean as the sole N source, in maize aerial parts at 20, 40, 60, 80 and 100 days after emergence. The differences observed are probably due to the two-month interval between the application of the compost and C. juncea, which increased the N available from C. juncea, the latest application.…”
Section: Leaf Nmentioning
confidence: 96%
“…In maize grown in pots and fertilized with C. juncea, there was no N immobilization caused by the legume, because of the relatively low C/N (Ambrosano et al, 2003 and2009). However, maize is an annual and shortcycle crop and would be less influenced by the remaining and more recalcitrant organic matter.…”
Section: Leaf Nmentioning
confidence: 99%